The EEC syndrome and SHFM: report of two cases and mutation analysis of p63 gene - Ergin, Hacer; Semerci, C Nur; Karakuş, Y Tuğrul; Scheffer, Hans; Ergin, Seniz; Koltuksuz, Uğur; Meijer, Rowdy; Satiroğlu-Tufan, N Lale (The Turkish Journal of Pediatrics, 2010)
The p63 gene is a transcription factor and a member of the p53 family. Heterozygote mutation of the p63 gene is suggested in a number of human syndromes including limb development and/or ectodermal dysplasia. The EEC syndrome, consisting of ectrodactyly (E), ectodermal dysplasia (E) and cleft lip (C) with or without cleft palate, is the prototype of these syndromes with the presence of heterozygote mutation in the p63 gene in most of the patients. Nonsyndromic split hand/foot malformation (SHFM) is one of the EEC-like syndromes, and the p63 gene mutation was reported in only a few patients. Five different loci have been mapped to date, but the etiology is yet to be explained in the rest of the patients. Here, we report two cases. Case 1, diagnosed with EEC syndrome, had type 2 urogenital sinus and a new heterozygous mutation of 934G>A (D312N) in exon 8 of the p63 gene. Case 2 was diagnosed as SHFM with no mutation in the p63 gene. Genotype and phenotype correlation of these two cases among the reported patients is discussed in this report.